Genetic Alterations and Transcriptional Expression of m6A RNA Methylation Regulators Drive a Malignant Phenotype and Have Clinical Prognostic Impact in Hepatocellular Carcinoma - Zhu, Gui-Qi; Yu, Lei; Zhou, Yu-Jie; Du, Jun-Xian; Dong, Shuang-Shuang; Wu, Yi-Ming; Shi, Ying-Hong; Zhou, Jian; Fan, Jia; Dai, Zhi (Frontiers in Oncology, 2020)
Background: N6-methyladenosine (m6A) RNA methylation, associated with cancer initiation and progression, is dynamically regulated by the m6A RNA regulators. However, its role in liver carcinogenesis is poorly understood. Methods: 371 hepatocellular carcinoma (HCC) patients from the Cancer Genome Atlas database with sequencing and copy number variations/mutations data were included. Survival analysis was performed using Cox regression model. Gene set enrichment analysis was performed to investigate the functions correlated with different HCC subgroups. Finally, we used machine-learning model to selected regulators for developing risk signature (m6Ascore). Results: We demonstrated that eleven m6A RNA regulators are significantly differentially expressed among 371 HCC patients stratified by clinicopathological features (P<0.001). We then identified two distinct HCC clusters by applying consensus clustering to m6A RNA regulators. Compared with cluster2 subgroup, the cluster1 subgroup correlates with poorer prognosis (P<0.001). Moreover, the cell cycle, splicesome and notch signaling pathway are significantly enriched in the cluster1 subgroup. We further derived m6Ascore, using four m6A regulators, predicting HCC prognosis well at three (AUC=0.7) or five years (AUC=0.7) in training or validation. Finally, we discovered that mutations and/or copy number variations of m6A regulators, conferring worse survival, are strongly associated with TP53 mutations in HCC. Conclusions: We find a significant relationship between the alterations and different expressions causing increased m6A level and worse survival, especially in TP53-mutated HCC patients. Genetic alterations of m6A regulatory genes may cooperate with TP53 and its regulator/downstream targets in the pathogenesis or maintenance of HCC. Our m6Ascore may be applied in the clinical trials for patient stratification in HCC.